2017
DOI: 10.3390/molecules22091566
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory and Anti-Oxidative Activities of Phenolic Compounds from Alnus sibirica Stems Fermented by Lactobacillus plantarum subsp. argentoratensis

Abstract: Fermentation of Alnus sibirica (AS) stems using Lactobacillus plantarum subsp. argentoratensis was conducted and three compounds isolated from the Alnus species were identified for the first time, 7-(3,4-dihydroxyphenyl)-1-(4-hydroxyphenyl)-heptan-3-one, 1-(3,4-dihydroxyphenyl)-7-(4-hydroxyphenyl)-heptan-3-one and 4-(3,4-dihydroxyphenyl)-butan-2-one, along with 14 known compounds. The anti-oxidative and anti-inflammatory abilities of AS and fermented AS (FAS) as well as the isolated phenolic compounds from FAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…IC 50 values were defined as the concentration needed to scavenge 50% free radicals. Ascorbic acid served as the positive control [38].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…IC 50 values were defined as the concentration needed to scavenge 50% free radicals. Ascorbic acid served as the positive control [38].…”
Section: Methodsmentioning
confidence: 99%
“…L-NMMA was used as a positive control. Inhibition of NO synthesis was calculated as inhibition rate (%) = [1 - (sample OD - blank OD)/(control OD - blank OD)] × 100, and the IC50 values were defined as concentrations that inhibit 50% of NO production [38].…”
Section: Methodsmentioning
confidence: 99%
“…Among them, muricarpon B (1), initially characterized in 2006 from Amomum muricarpum (Zingiberaceae), 22 was isolated by Korean Min-Won Lee's team from fermented barks of Alnus sibirica (Betulaceae) and reported intensive biological studies to evaluate its anti-inflammatory activity. According to the various reported studies, it showed potent antioxidant activities in DPPH radical scavenging assays with IC50 values of 20.1 M, 23 24.1 M 24 and 38.7 M 25 (compared to AA: IC50 = 46.0, 23 24.8 24 and 44.7 25 M respectively), NBT superoxide radical scavenging effect with IC50 values of 30.1 M 24 and 12.7 M 25 (compared to allopurinol as positive control, IC50 = 8 24 and 3.9 25 M respectively) and strong NO production inhibitory activity with IC50 values of 6.6 M, 23 which could be explained by non-specific Michael addition reactions. 27 Hirsutenone (2) was also widely evaluated against cytokines production and proteins expression.…”
Section: Linear Natural Diarylheptanoidsmentioning
confidence: 97%
“…Stereochemistry is reported as mentioned in the original articles. Alnus sibirica [23][24][25] Alnus formosana 27 Alnus japonica 28,[30][31][32]33 Alnus hirsuta 29 Alnus tinctoria 34 -…”
Section: Linear Natural Diarylheptanoidsmentioning
confidence: 99%
See 1 more Smart Citation